A comparative proteomic study of sera in paediatric systemic lupus erythematosus patients and in healthy controls using MALDI-TOF-TOF and LC MS-A pilot study - Rana Anita; Minz Ranjana W; Aggarwal Ritu; Sharma Sadhna; Pasricha Neelam; Anand Shashi; Singh Surjit (BMC, 2012)
Abstract Background Paediatric systemic lupus erythematosus (pSLE) exhibits an aggressive clinical phenotype with severe complications and overall poor prognosis. The aim of this study was to analyse differential expression of low molecular weight (LMW) serum protein molecules of pSLE patients with active disease in comparison to sera of healthy age matched controls. Further, some of the differential expressed spots were characterised and identified by Matrix Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry (MALDI-TOF-MS) and liquid chromatography (LC-MS). Methods 2D-PAGE was performed using pooled sera of active pSLE and age matched healthy controls. Gels were silver-stained and differentially expressed protein spots were detected by automated image master platinum 2D software. 79 ± 17 protein spots were detected for control gels and 78 ± 17 protein spots for patient gels. Of these eleven protein spots were selected randomly and characterized by MALDI-TOF MS (five protein spots) and LC MS (six protein spots) techniques. Results Out of the 11 protein spots, 5 protein spots were significantly upregulated viz., leiomodin 2 (LMOD2); epidermal cytokeratin 2; immunoglobulin kappa light chain variable region; keratin 1 and transthyretin (TTR). Three protein spots were significantly down regulated e.g., apolipoprotein A1 (APOA1); chain B human complement component C3c; campath antibody antigen complex. Two protein spots (complement component C3; retinol binding protein (RBP) were found to be expressed only in disease and one protein spot cyclohydrolase 2 was only expressed in controls. Conclusions We conclude that 2-D maps of patients with active pSLE and controls differ significantly. In this pilot study, using proteomic approach we have identified differential expressed proteins (of LMW) e.g., RBP, LMOD 2, TTR, Component C3c Chain B and APO A1. However, in future, further studies need to confirm the physiological and pathological role of these proteins in similar cohorts of pSLE.